The Bible: The Greatest Marketing Tool Ever Written - Beck, Bernard (Hamilton Books, 2010)
The Bible: The Greatest Marketing Tool Ever Written explores the question: 'Why was the Bible written?' Beck concludes that the Bible's authors wanted to enable the nascent Hebrew tribes to coalesce into a nation, and compares their efforts to the recommendations of top modern-day marketing authorities, illustrating the prescient marketing effort in the Bible. Beck demonstrates ways that the authors of the Bible chose the most efficient and effective channels for transmitting their still-relevant message. This historical study and education tool, whose clear explanation of marketing techniques can be applied to the most challenging twenty-first century marketing opportunities, presents points of conversation to individuals of all faiths.